2020
DOI: 10.1055/s-0039-1697994
|View full text |Cite
|
Sign up to set email alerts
|

Functional Impact of Tinnitus in Patients with Hearing Loss

Abstract: Introduction Tinnitus, which is considered the third worst symptom for humans, is a common complaint among people living with hearing loss and may negatively affect the quality of life of those who have it. Objective To analyze the perception of the handicap in patients with tinnitus and hearing loss as well as the possible associations between the variables hearing loss, loudness, onset, frequency and annoyance by tinnitus, and the correlation between the visual analogue scale (VAS) and the Tinnitus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
3
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 29 publications
3
3
0
2
Order By: Relevance
“…These findings are similar to those of another study, 27 in which most participants were females and reported symptoms of bilateral tinnitus, and a mean time of symptom perception of 7.8 years. Data in the present study also corroborate findings from a study by Mantello et participants reported bilateral tinnitus, 28 as well as the findings of studies by other authors studies, with $ 60% of the sample comprising females. 28,29 It should be noted that it is not usual for females to be more prevalent among samples of tinnitus patients, although there are some studies with that distribution.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…These findings are similar to those of another study, 27 in which most participants were females and reported symptoms of bilateral tinnitus, and a mean time of symptom perception of 7.8 years. Data in the present study also corroborate findings from a study by Mantello et participants reported bilateral tinnitus, 28 as well as the findings of studies by other authors studies, with $ 60% of the sample comprising females. 28,29 It should be noted that it is not usual for females to be more prevalent among samples of tinnitus patients, although there are some studies with that distribution.…”
Section: Discussionsupporting
confidence: 93%
“…Data in the present study also corroborate findings from a study by Mantello et participants reported bilateral tinnitus, 28 as well as the findings of studies by other authors studies, with $ 60% of the sample comprising females. 28,29 It should be noted that it is not usual for females to be more prevalent among samples of tinnitus patients, although there are some studies with that distribution. 1,4,6,8 Most participants were identified with hearing loss (76.5% in the left ear and 82.4% in the right ear), corroborating a study that indicated tinnitus as being associated with subjects with a diagnosis of hearing loss.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Es importante aclarar, que se registraron los datos de pacientes con sensación de hipoacusia y con hipoacusia objetiva. Los primeros, fueron pacientes que referían sentir hipoacusia unilateral o bilateral en concomitancia al inicio de su tinnitus, independiente de los resultados de su audiometría y la hipoacusia objetiva fue definida como una audiometría de transmisión, neurosensorial o mixta, con una pérdida mayor o igual a 20 decibeles 11 . El 33% de los pacientes refiere sentir hipoacusia concomitante a su tinnitus.…”
Section: Resultsunclassified
“…En relación a la frecuencia, en dos tercios de los pacientes, el tinnitus fue continuo y en un tercio intermitente, esto no se relaciona con la literatura donde la mayor frecuencia es en el patrón intermitente con 60% 14 . Sin embargo, en un estudio del año 2020, llevada a cabo por Mantello y colaboradores en un hospital general de Sao Paulo, Brasil, encontraron un patrón bilateral en el 60% de los casos y un patrón continuo en el 80%, siendo similares valores en relación al presente estudio, pero debido a que su muestra solo eran 30 pacientes puede no ser representativo ni generalizable a la población 11 . En relación a las comorbilidades del tinnitus, en la literatura se encuentran amplias asociaciones, pero sin un sustento evidente, se cree que su causa es multifactorial.…”
Section: Discussionunclassified